Nexus of the Load Bearing Capacity of Rails and the Stiffness of the Optimized Sleepers. (2016) - Köllő, Szabolcs Attila; Köllő, Gavril; Puskás, Attila
Abstract: In the railway track modernizations an important role is played by the connection between the sleepers and the rails. In this article the authors are studying the effect of the sleepers on the rails in the ballasted railway superstructure, considering the ballast layer properties according to local conditions, but unchanged during the studies. The optimised dimensions of the sleepers are aimed in order to allow increased speed of the railway. The role of the sleepers mainly consists in taking over the load on the rails and transmitting to the ballast, therefore technical capabilities are highly influenced also by the behaviour of the other elements of the rail track system.